(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The metal Ion Pollution are big challenges for environment and Health Effects . The majorconcern health hazards metals are lead , Arsenic, Mercury, Chromium,Cadmium,Silver, Anti mony andtheir compounds. The air, water , and soil or the living places may be contaminated with toxic chemicalsand substances. In the current scenario the human beings Facing the many environmental issues andchallengs due to the adverse effect of toxic metals and chemicals on our air, water, and soil quality also.The india is a developing country and have facing different – different problems on our ecological andenvironmentalissues . Hence I will decided to make an analytical Chemist , and then my current work toform the sensors based on heterogeneous membrane of macrocyclic compounds.The Macrocyclic compounds are those molecules and ions containing a ring of twelve or more atmos.Like –Lactem, Lactones, Ligands, Porphyrinsetc.The God have already gifited five sensors to humanbeing like –eyes, Ears, Nose, Tongue and Skin etc.